2017
DOI: 10.1371/journal.pone.0178336
|View full text |Cite
|
Sign up to set email alerts
|

Establishment a real-time reverse transcription PCR based on host biomarkers for the detection of the subclinical cases of Mycobacterium avium subsp. paratuberculosis

Abstract: Bovine paratuberculosis (PTB) is a chronic enteric inflammatory disease of ruminants caused by Mycobacterium avium subsp. paratuberculosis (MAP) that causes large economic losses in the dairy industry. Spread of PTB is mainly provoked by a long subclinical stage during which MAP is shed into the environment with feces; accordingly, detection of subclinical animals is very important to its control. However, current diagnostic methods are not suitable for detection of subclinical animals. Therefore, the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…The transmission of MAP from dam to offspring by horizontal as well as vertical routes in MAP non-vaccinated cattle (major role: [36][37][38], minor role: [39]), goats, and sheep [31] has been researched in a number of studies. A meta-analysis in cattle quantifying age-and dose-dependence of early and late shedding of MAP indicated that challenging older calves or using multiple-exposure experimental systems resulted in a smaller proportion and shorter duration of early shedding as well as slower transition to late shedding from latent compartments [40].…”
Section: Discussionmentioning
confidence: 99%
“…The transmission of MAP from dam to offspring by horizontal as well as vertical routes in MAP non-vaccinated cattle (major role: [36][37][38], minor role: [39]), goats, and sheep [31] has been researched in a number of studies. A meta-analysis in cattle quantifying age-and dose-dependence of early and late shedding of MAP indicated that challenging older calves or using multiple-exposure experimental systems resulted in a smaller proportion and shorter duration of early shedding as well as slower transition to late shedding from latent compartments [40].…”
Section: Discussionmentioning
confidence: 99%
“…Th1 response decreases as the disease progresses, but the antibody response (Th2 response) to MAP increases (13). Thus, since the Th1 / Th2 shift is related to disease progression and bacterial excretion, many studies have determined the MAP infection stage based on detection of MAP and MAP-specific antibody in specimen such as feces, milk, and sera (12,14,15). DNA-detected with ELISA-negative, and was expected to be detectable at the early state of MAP infection.…”
Section: Discussionmentioning
confidence: 99%
“…Among the differentially regulated genes with potential as diagnostic biomarkers in mycobacterial infections are Tfrc, which encodes the transferrin receptor, and LTF, which regulates lactoferrin; they are often attributed to the pathogen's metabolism of host iron via the action of mycobactins (74)(75)(76). Similarly, S100a8 and S100a9 are differentially regulated and have been proposed as biomarkers for comparable inflammatory bowel diseases (75,76).…”
Section: Downloaded Frommentioning
confidence: 99%
“…This response is thought to be a result of the host's immune system limiting the harmful immunopathology of MAP infection. Matrix metalloproteinase 9 (MMP9) and its inhibitor TIMP1, are both upregulated during paratuberculosis and TB and are documented as consistently up-regulated genes in TB (74,75,79). Two β-defensin genes have also recently been shown to be up-regulated in MAP, Defb1 and Defb10, indicating that their antimicrobial and immunomodulatory role may be indicative of host responses to bacterial infection (74).…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation